FLOWERING PLANT DIVERSITY AND ETHNOBOTANY OF MORNI HILLS, SIWALIK RANGE, HARYANA, INDIA - NIDHAN SINGH; B.D. VASHISTHA (International Journal of Pharma and Bio Sciences, 2014)
The present work, an attempt to prepare an inventory of floristically richest part of Haryana, was chiefly carried out from November 2000 till March 2005 and the area under study has been studied extensively to find out the diversity of flowering plants in the area, local utilizations of the plants, their ecological status and associations, if any. Attempt has also been made to correlate the findings with the earlier works carried out in the state or adjoining regions